The Challenges towards Chinese Outward Foreign Direct Investments in the UK - Jones, Nicholas (2007)
China in recent years has emerged has emerged as a major player in the global economic scene and has managed to attract a significant amount of foreign direct investment (FDI). However, China's outward FDI has achieved much less acknowledgement. Mainstream theories of internationalisation do not necessarily apply to the Chinese context that is derived from Western theories. Through an entrepreneurial drive Chinese organisations desire to obtain Western practices and assets that a hybrid framework of analysis is needed to construct an understanding of Chinese outward FDI. This study investigates Chinese organisations competitive advantages and why they internationalise in such markets as the UK. The challenges that Chinese multinational corporations will face when branching out into developed markets shall be explored in terms of HRM practices and implications as well as the perceived image of Chinese organisations. The study concludes with the notion that the challenges that Chinese firms face are the lack of understanding of Chinese management theory.